Performance of MSK with Walsh Coding - Bria, Oscar Norberto (2024)
In this work, the performance of the combination of MSK (Minimum Shift Keying) modulation and Walsh coding is analysed using analytical results and simulation. MSK with Walsh coding is employed in applications like Mode 5 to ensure secure military communications.